2022
DOI: 10.1016/j.omto.2021.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The NRF2-dependent transcriptional axis, XRCC5/hTERT drives tumor progression and 5-Fu insensitivity in hepatocellular carcinoma

Abstract: Human telomerase reverse transcriptase (hTERT) is highly expressed in many tumors and is essential for tumorigenesis and metastasis in multiple cancers. However, the molecular mechanisms underlying its high expression level in hepatocellular carcinoma (HCC) remain unclear. In this study, we identified X-ray repair cross-complementing 5 (XRCC5), a novel hTERT promoter-binding protein in HCC cells, using biotin-streptavidin-agarose pull-down assay. We found that XRCC5 was highly expressed in HCC cells, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In addition to the interrelationships of proteasome-hTERT and proteasome-NRF2 system, there are several studies about the bilateral relations between hTERT and NRF2. XRCC5 (X-ray repair crosscomplementing 5), a transcriptional regulator factor binding to the hTERT promoter, was reported to physically interact with NRF2, which in turn upregulated hTERT in an NRF2 dependent manner in hepatocellular carcinoma (HCC) cells [83]. Consistently, administration of (caption on next column) Fig.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to the interrelationships of proteasome-hTERT and proteasome-NRF2 system, there are several studies about the bilateral relations between hTERT and NRF2. XRCC5 (X-ray repair crosscomplementing 5), a transcriptional regulator factor binding to the hTERT promoter, was reported to physically interact with NRF2, which in turn upregulated hTERT in an NRF2 dependent manner in hepatocellular carcinoma (HCC) cells [83]. Consistently, administration of (caption on next column) Fig.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to the interrelationships of proteasome-hTERT and proteasome-Nrf-2 system, there are several studies about the bilateral relations between hTERT and Nrf-2. XRCC5 (X-ray repair cross-complementing 5), a transcriptional regulator factor binding to the hTERT promoter, was reported to physically interact with Nrf-2, which in turn upregulated hTERT in an Nrf-2 dependent manner in hepatocellular carcinoma (HCC) cells (Liu et al, 2022). Consistently, administration of DMF, an activator of Nrf-2 pathway, to mice resulted in significant elevation of TERT mRNA levels (Akino et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the mTORC1 pathway and activation of Nrf2 are other mechanisms by which curcumin could increase the lifespan of normal cells. Recent data have indeed shown that Nrf2 interacts with X-ray repair cross complementing 5 and regulates hTERT expression, increasing chromosome integrity and genome stability for long-term proliferation [ 139 ]. Overall, a multitude of in vivo, in vitro , and clinical studies have confirmed the protective role of curcumin via Nrf2 regulation, which in turn could maintain telomere integrity [ 118 , 140 ].…”
Section: Potential (Poly)phenol Targets In Senescent and Cancer Cellsmentioning
confidence: 99%